Simultaneous Task Subdivision and Allocation Using Negotiations in Multi-Robot Systems. (4th March 2015) - Rossi, Claudio; Aldama, Leyre; Barrientos, Antonio
This paper presents a negotiations-based approach for simultaneous task subdivision and assignment in heterogeneous multi-robot systems. We first propose an abstraction of the concept of a task that allows for the generalizing of a variety of different problems. Based on such an abstraction, we have developed a negotiation protocol based on Rubinstein's alternate offers protocol. This is extended to the multi-dimensional space and employs a heuristic search step for evaluating and generating offers. Furthermore, the issue of how to extend a bilateral negotiations protocol to more than two parties is taken into consideration. The protocol was first tested in numerical simulations with different scenarios and then applied to three real-world missions.